AB0131 Abnormality of Mesenchymal Stem Cells in Patients with Rheumatoid Arthritis. (10th June 2014) - Sun, Y.; Liu, R.; Chen, W.; Feng, X.; Sun, L.
Abstract : Background: It has been shown that human umbilical cord mesenchymal stem cells (MSCs) could provide some benefits for the treatment of rheumatoid arthritis (RA) patients with refractory disease. Objectives: The aim of this study is to explore whether the MSCs from bone marrow in RA patients are defective and dysfunctional. Methods: We evaluated the proliferative potential of MSCs in 7 days of culture. Cellular apoptosis, immigration and senescence were detected by using 7-AAD flow-cytometry, transwell assay and the senescence-associated β-galactosidase (SA-β-Gal) staining respectively. Cultured supernatants of MSCs from RA patients and healthy controls (HC) were collected, and analyzed for cytokine production using a protein array. The immunomodulatory capacity of MSCs on PBMCs proliferation and on the distribution of Th17, Treg and Tfh cells was also investigated. Results: The growth rate was lower in RA MSCs than that in HC MSCs. RA MSCs had deficient migration ability compared to HC MSCs after 24 hours of culture. More SA-β-Gal stained cells were observed in RA MSCs, and the expression of cell cycle inhibitor p21 was higher in RA MSCs than HC MSCs. However, no significant differences were found between RA MSCs and HC MSCs in the percentage of early apoptotic and late apoptotic cells. Protein arrays showed no significant differences in the cytokine production between RA MSCs and HC MSCs. MSCs from both the RA patients and controls were able to suppress the proliferation of PBMCs, and no significant differences were found between RA MSCs and HC MSCs in regulating Treg and Tfh cells. However, the ability to inhibit Th17 cells was impaired in MSCs from RA patients. Conclusions: MSCs in RA patients have abnormalities compared to those in healthy control, which may play an important role in the development of RA disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2194